2018
DOI: 10.23969/jp.v2i2.557
|View full text |Cite
|
Sign up to set email alerts
|

A Meningkatkan Kemampuan Membaca Pemahaman Berbantuan Pembelajaran Tematik Terpadu Bernuansa Model Interactive-Compensatory.

Abstract: ABSTRACT Based on the preliminary study, it revealed that the 5th grade students in some elementary schools in Bandung Regency had low ability to perform reading comprehension. This can be seen from students’ low ability to express explicit meanings, define main idea, search for keywords,  retell the contents of the text with their own words, create a concept map, and understand the message of the author. Based on this finding, there is a need to develop instructional devices based on specific learning m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Dengan adanya kemampuan membaca pemahaman siswa akan lebih mudah belajar memahami pembelajaran, tidak hanya di sekolah, tetapi juga di luar lingkungan sekolah, sehingga dapat meningkatkan pengetahuan siswa (Nirmala, 2019). Proses membaca pemahaman dilakukan untuk memahami dan menemukan makna yang terkandung dalam bahan bacaan (Nirmala, 2019;Puspita & Rahman, 2018;Rahmi & Marnola, 2020). Tanpa memahami bacaan dan memaknainya, proses pembelajaran tidak akan bisa berjalan dengan mudah.…”
Section: Pendahuluanunclassified
“…Dengan adanya kemampuan membaca pemahaman siswa akan lebih mudah belajar memahami pembelajaran, tidak hanya di sekolah, tetapi juga di luar lingkungan sekolah, sehingga dapat meningkatkan pengetahuan siswa (Nirmala, 2019). Proses membaca pemahaman dilakukan untuk memahami dan menemukan makna yang terkandung dalam bahan bacaan (Nirmala, 2019;Puspita & Rahman, 2018;Rahmi & Marnola, 2020). Tanpa memahami bacaan dan memaknainya, proses pembelajaran tidak akan bisa berjalan dengan mudah.…”
Section: Pendahuluanunclassified
“…Therefore, the instilling of regional culture through education is a strategic step to improve the quality of future generations who are noble and virtuous. The study of local cultural wisdom needs to be developed in education because it has the benefit of giving birth to generations of competent and dignified people, reflecting cultural values, participating in building the national character, contributing to the creation of identity nation, and take part in preserving national culture [22], [23], [25] [26].…”
Section: Jampé-jampé Harupat Jampé-jampé Harupat Geura Gedé Geura Lumpatmentioning
confidence: 99%
“…Second, the teaching material for reading comprehension used in the fifth grade of the elementary school still did not bring students to imagine what they are reading because in the teaching materials they did not pay attention to reading comprehension techniques. Most students read by voicing the text they read so that their lips move (Chandra et al, 2019;Cheng, 2014;Puspita & Rahman, 2017). Another movement was found that students moved their heads following the reading lines when reading comprehension, and pointed at the lines of reading with fingers.…”
Section: Introductionmentioning
confidence: 99%